Analysis of the Influence of Psychosocial Support on the Quality of Life of Patients with Chronic Diseases - Stev, Cheline Hertina (Institute of Accounting Research and Novation (IARN), 2025)
This research examines the influence of psychosocial support on the quality of life (QoL) of patients with chronic illnesses. Recognizing that chronic diseases can significantly impair both physical and emotional well-being, this study aims to elucidate the multifaceted roles that family, healthcare providers, and community networks play in enhancing QoL among affected individuals. Using a mixed-methods approach, data were collected from a diverse sample of chronic illness patients through surveys and interviews, focusing on the impact of different types of psychosocial support on various QoL domains: physical, psychological, social, and environmental. The findings reveal a strong positive correlation between psychosocial support and QoL, with family support being particularly effective in improving psychological and social well-being, while healthcare provider support significantly impacts physical health outcomes. Community support was also found to enhance social connections and emotional resilience, underscoring the importance of a holistic approach to chronic illness management. Despite challenges such as subjective variations in QoL measures and diverse support needs across different chronic conditions, the results advocate for the integration of comprehensive support programs within healthcare systems. This study contributes to the existing literature by providing a nuanced understanding of how various forms of psychosocial support uniquely influence QoL in chronic illness patients. The implications for healthcare practices and policies emphasize the need for tailored interventions that address the diverse and evolving needs of patients, ultimately fostering resilience and promoting better health outcomes.